Modeling the mechanical behavior of a helmeted headform impacted with a laminated windshield with consideration of composite failure. (1st January 2022) - Gao, Wei; Wang, Jiawen; He, Xiaoqiang; Feng, Y.T.; Chen, Shunhua; Wang, Chengyong
Abstract: In a bicycle–vehicle or a motorcycle–vehicle accident, the head of an adult rider with a helmet is very likely to impact the windshield laminated glass. Such a complex impact phenomenon normally involves head injury, windshield failure, and helmet damage. The main purpose of this work is to present a computational framework for modeling the impact interaction between a helmeted headform and a windshield glazing. To achieve this, a finite element helmet model is established, where a crushable foam model and a continuum damage mechanics based fracture model are used to describe helmet composite failure. The accuracy of the model is validated by comparing the numerical results with the corresponding experimental data. For the windshield failure, we adopt the commonly used intrinsic cohesive zone model to account for two main failure patterns, i.e., glass fracture and glass–PVB debonding. The mechanical responses of a helmeted headform are compared with those of a pure headform to investigate the protective performance of the helmet. Finally, parametric studies are carried out to numerically investigate the effects of impact velocity, helmet posture, and impact location on the windshield on headform response.